Fundraising strategy in reaching implementation targets community care programs at the Solo Peduli Foundation - Akshah, Coiromi; Yuliar, Ade; Andraeny, Dita (Journal of Islamic Economics Management and Business (JIEMB), 2022)
Zakāt institutions currently play a role in helping the government overcome poverty through humanitarian programs. This research aims to determine fundraising strategies that the Solo Peduli Foundation is doing so that their humanitarian programs can run. The type of research conducted by the author is field research by taking the research location at the Solo Peduli Foundation and using a qualitative descriptive approach. Data collection methods are by interview and observation. The online fundraising strategy is done through digital methods to make it easier for donors to donate and transfer via ATM/mobile banking. Offline fundraising is carried out by donating funds directly and participating in seminars, recitations, and other activities involving many people. In offline fundraising, the main strength is the direct collection of funds assisted by caring ambassadors. Besides that, several obstacles are still faced in fundraising, namely regarding execution commitments, overcoming resistance, selling (selling/conveying information), and digitalization. Furthermore, the fundraising strategy in mobilizing humanitarian programs is felt to be quite effective in helping people who are in poverty.Keywords: fundraising strategy; poverty; program.